Moisture Absorption Analysis of Linear-Low-Density-Polyethyelene Natural-Rubber Nanocomposite for HV Insulation - M.S. Kamarulzaman; N.A. Muhamad; N.A.M. Jamail; M.A.M. Piah; M.A.B. Sidek; N.F. Kasri (IAES Indonesia Section, 2014)
Insulation for high voltage (HV) application such as cable subjected to several types of degradation. These degradation can lead to premature breakdown and when its happen cost to replace or repair equipment will be higher. Many research was done to improve the insulation properties and currently nanocomposite material get serious attention due to their abilities to enhance electrical performance by addition of nanofiller into the based material. In this paper, water absorption of Linear-Low-Density-Polyethyelene (LLDPE) with different amount of nanofiller composition is studied. This study is necessary to be conducted since polymer based material is the most common insulation material used in HV cable. The HV cable normally will be continuously exposed in uncontrolled environment. Because of this, the cable will exposed to watery condition and it is crucially needed for the insulation to remain dry to the cable performance. Three types of nanofillers at different weight percentage (%wt) added into LLDPE, was used in this study are: Silicon dioxide (SiO2), Titanium dioxide (TiO2) and Monmorillonite (MMT). Percentage absorption of water was measured according to BS 6470 until the samples reaches saturation level. Experimental result demonstrate that SiO2 absorb less water than other filler while, the MMT has hydrophilic properties which it absorb more water compare to another sample. By used appropriate composition and type of nanofiller, a good insulator that are resistant to environmental influence can be produced